Compatibilizer influence on the empty fruit bunch-polypropylene composites / Mohamad Jani Saad, Rozman Din and Zainal Arifin Mohd Ishak - Saad, Mohamad Jani; Din, Rozman; Mohd Ishak, Zainal Arifin (2006)
The mixing between the empty fruit bunches fibres and the polypropylene along with aid of the competibilizer agents pertaining to solve the incompatibility within these different phases and nature has been successfully carried out. By doing these styles, the hydroxyl groups on the fibres surfaces should be bridged to the methyl groups of the polypropylene through the compatibilizer role as the middle part. The treatment on the respective composites by using maleic anhydride for enhancing the board performance can be utilized on the EFB prior to bind with a polypropylene as a binder. The effects of MAH treatment on the composites were analyzed by scanning electron microscopy (SEM) to look at the adhesion region or the interfacial parts. The SEM results became a site evidence of the good performance from board that treated compared to the untreated ones along with the mechanical or other relevance tests results.